Horatio's drive America's first road trip - Duncan, Dayton; Burns, Ken, 1953-; Keith, David; Hanks, Tom.; Arkin, Adam.; Bodett, Tom.; Bosco, Philip; Conway, Kevin; Cullum, John, 1930-; Guyer, Murphy; Madigan, Amy.; Plimpton, George; et al. ([United States] : PBS Home Video ; Hollywood, CA : Distributed by Paramount Home Entertainment, 2004)
Horatio Nelson Jackson, an eccentric Vermont doctor, drove from San Francisco to New York City, in 1903 to became the first person to drive an automobile across the continent - a feat never before accomplished. It would mark the beginning of a new era in America and the end of another. It took Lewis & Clark over two years to go from the Atlantic to the Pacific - Horatio went the opposite direction, by means of the "Horseless carriage", in less than 3 months.
DVD, region 1, Dolby surround stereo., NTSC.
In English; closed-captioned.
Narrated by Keith David ; Voices: Tom Hanks, Adam Arkin, Tom Bodett, Philip Bosco, Kevin Conway, John Cullum, Murphy Guyer, Amy Madigan, George Plimpton, Eli Wallach.
Cinematography, Allen Moore, Ken Burns ; editor, Erik Ewers.
Originally broadcast in 2003.
MPAA rating: Not rated.
Keywords: Jackson, Horatio Nelson, -- 1872-1955.; Automobile travel; Automobiles; United States -- Description and travel; Feature films; Documentary films; Films for hard of hearing people; Automobile travel -- United States -- History -- 20th century; Documentary videos; Video recordings for hard of hearing people